Physical soil fertility in the sowing system in wachado on Nariño, Colombia - Volverás-Mambuscay, Belisario (2020)
Introduction. In the wachado system, the soil used is continuously rotated with potatoes (one or two harvests) and pasture for dairy cattle (two to three years). Wachado is a pre-Columbian production system that only uses a manual tool, and is practiced and conserved by indigenous communities on Andean slopes of Colombia, Peru, and Ecuador. The system is relegated by the intensive mechanization systems in which research predominates, unlike the wachado research where it is scarce. Objective. To evaluate the effect of sowing in wachado on the state of some physical properties of the soil. Materials and methods. The work was carried out in three locations in the department of Nariño, Colombia, between January and March 2015. In each locality, soil samples were taken at different depths, and rain simulations were performed in triplicate to determine volumetric, water regulation, structural stability, and texture indicators in plots that were on pasture for three years. Results. After thirty years of use, the wachado soil retained a low apparent density (0.41 to 0.91 g cc-1), high total porosity (56 % to 70 %), high moisture content at low, and high suctions (75 % and 40 %). In addition, moderate structural stability (DPM greater than 1.5), 60 % microporosity, low infiltration (19 % to 33 %), and high runoff (66 % to 81 %) were found. Conclusion. After thirty years of potato cultivation under the wachado system, the values of the physical indicators of the soils showed that the minimum tillage and the potato/grass rotation, reduced soil degradation and regulated the hydric condition.